EVALUATION OF BITMAP INDEX USING PROTOTYPE DATA WAREHOUSE - Hamad, Murtadha M.; Raheem, Muhammed Abdul (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Bitmap indices have become popular access methods for data warehouse applications and decision support systems with large amounts of read-mostly data. This paper could arrive a number of results such as ; Bitmap Index highly improves the performance of Query Answering in Data Warehouses, It highly increases the efficiency of Complex Query processing through using bitwise operations (AND, OR). A prototype of Data Warehouse â€œSTUDENTS DWâ€ has been built according to the conditions of W. Inomn of Data Warehouses. This prototype is built for student's information.